What gastroenterologists should know about SARS–CoV 2 vaccine: World Endoscopy Organization perspective. Issue 7 (8th June 2021) - Spadaccini, Marco; Canziani, Lorenzo; Aghemo, Alessio; Lleo, Ana; Maselli, Roberta; Anderloni, Andrea; Carrara, Silvia; Fugazza, Alessandro; Pellegatta, Gaia; Galtieri, Piera Alessia; Hassan, Cesare; Greenwald, David; et al.
Abstract: Background: The novel Coronavirus (SARS‐CoV‐2) has caused almost 2 million deaths worldwide. Both Food and Drug Administration and European Medicines Agency have recently approved the first COVID‐19 vaccines, and a few more are going to be approved soon. Methods: Several different approaches have been used to stimulate the immune system in mounting a humoral response. As more traditional approaches are under investigation (inactivated virus vaccines, protein subunit vaccines, recombinant virus vaccines), more recent and innovative strategies have been tried (non‐replicating viral vector vaccines, RNA based vaccines, DNA based vaccines). Results: Since vaccinations campaigns started in December 2020 in both the US and Europe, gastroenterologists will be one of the main sources of information regarding SARS‐CoV 2 vaccination for patients in their practice, including vulnerable patients such as those with Inflammatory Bowel Disease (IBD), patients with chronic liver disease, and GI cancer patients. Conclusions: Thus, we must ourselves be well educated and updated in order to provide unambiguous counseling to these categories of vulnerable patients. In this commentary, we aim to provide a comprehensive review of both approved COVID‐19 vaccines and the ones still under development, and explore potential risks, benefits and prioritization of vaccination.